Experimental Investigation on Joint Effects in Rock Cutting with a Conical Pick Under Unrelieved Cutting Conditions - Han-Eol Kim; Min-Seong Kim; Wan-Kyu Yoo; Chang-Yong Kim; Ji-Seok Yun (Applied Sciences)
In this study, a series of unrelieved cutting tests was conducted to analyze the effect of joints on rock cutting using a conical pick. The tests were performed on jointed rock mass specimens with joint spacings (Js) of 30, 60, and 90 mm and at cutting depths of 3, 6, 9, and 12 mm. For each case, the distance between the cutting path and the joint plane (d) was varied from 0.1Js to 0.5Js. The cutting force decreased as the distance from the joint plane increased but reached the level observed in intact rock at the midpoint between adjacent joint planes (d = 0.5Js). Regardless of joint spacing, the cutting force reached its minimum when d was between 0.2Js and 0.3Js. The rock fragmentation zone extended beyond the joint plane when d was 0.1Js but became confined within the joint plane from around 0.2Js to 0.3Js. These results indicate that the influence of the joint is most pronounced within this range. Three types of crack propagation patterns were observed near the joint plane: (1) cracks that terminate at the joint along the shortest path, (2) cracks that pass through the joint and reach the opposite free surface, and (3) cracks that end at a free surface located just inside the joint plane. These observations suggest that the reduction in cutting force can be attributed to shorter crack propagation paths due to the presence of the joint. This study contributes to a better understanding of the cutting behavior of jointed rock masses when using a conical pick.